The Influence of Social Capital on Sustainable MICE: The Role of Communication in Collaboration as a Mediator - Fitri, Nursiah; Pasaribu, Ika Mary; Surbakti , Enda Yunita; Jumjuma; Nasution , Azrina Sufi (INJECT (Interdisciplinary Journal of Communication), 2026)
This study aims to develop and validate a communication model in stakeholder collaboration for the sustainable implementation of MICE (Meetings, Incentives, Conventions, and Exhibitions) events in Medan City. The MICE industry plays a crucial role in driving regional economic growth; however, its sustainable implementation still faces challenges related to weak synergy and coordination among stakeholders. The lack of communication strategies in collaboration has resulted in suboptimal implementation of sustainability principles across various economic, social, and environmental dimensions. This study uses a quantitative approach, with data analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The variables studied include social capital (consisting of cognitive, relational, and structural dimensions), stakeholder collaboration through communication strategies, and the sustainability of MICE events. Data were collected through a survey of MICE industry players in Medan City. The results show that cognitive capital and relational capital have a positive and significant influence on the effectiveness of stakeholder communication and collaboration, while structural capital has a positive but insignificant influence. Furthermore, communication in stakeholder collaboration significantly influences the sustainability of MICE events and is shown to mediate the relationship between social capital and event sustainability. The total effects analysis shows that stakeholder collaboration serves as a key link strengthening the contribution of social capital to event sustainability. The R² value for communication in stakeholder collaboration is 0.663 and for event sustainability is 0.655, indicating strong explanatory power of the model. Furthermore, the Goodness of Fit (GoF) value of 0.57 indicates good model fit.